Long-term protection against a virulent field isolate of infectious laryngotracheitis virus induced by inactivated, recombinant, and modified live virus vaccines in commercial layers. Issue 3 (4th May 2019) - Palomino-Tapia, Victor A.; Zavala, Guillermo; Cheng, Sunny; García, Maricarmen
ABSTRACT: Infectious laryngotracheitis (ILT) is an acute respiratory disease of chickens controlled through vaccination with live-modified attenuated vaccines, the chicken embryo origin (CEO) vaccines and the tissue-culture origin (TCO) vaccines. Recently, novel recombinant vaccines have been developed using herpesvirus of turkey (HVT) and fowl pox virus (FPV) as vectors to express ILTV immunogens for protection against ILT. The objective of this study was to assess the protection efficacy against ILT induced by recombinants, live-modified attenuated, and inactivated virus vaccines when administered alone or in combination. Commercial layer pullets were vaccinated with one or more vaccines and challenged at 35 (35 WCH) or 74 weeks of age (74 WCH). Protection was assessed by scoring clinical signs; and by determining the challenge viral load in the trachea at five days post-challenge. The FPV-LT vaccinated birds were not protected when challenged at 35 weeks; the HVT-LT and TCO vaccines in combination provided protection similar to that observed in chickens vaccinated with either HVT-LT or TCO vaccines when challenged at 35 weeks, whereas protection induced by vaccination with HVT-LT followed by TCO was superior in the 74 WCH group compared with the 35 WCH group. Birds given the inactivated ILT vaccine had fewer clinical signs and/or lower viral replication at 74 WCH when combined with TCO or HVT-LT, but not when given alone. Finally, the CEO-vaccinated birds had top protection as indicated by reduction of clinical signs and viral replication when challenged at 35 weeks (74 weeks not done). These results suggest that certain vaccine combinations may be successful to produce long-term protection up to 74 weeks of age against ILT.